Comparative Transcriptome Analysis Reveals Changes in Gene Expression Associated with Anthocyanin Metabolism in Begonia semperflorens under Light Conditions - Kunkun Zhao; Airong Liu; Yuanbing Zhang; Weixin Liu; Zhimin Zhao; Shuyue Yang (Horticulturae, 2024)
Anthocyanins, recognized as stress indicators, particularly under high-light conditions, play a pivotal role in plant stress responses. The advent of transcriptomics has opened avenues to elucidate the mechanisms underlying high light-induced anthocyanin biosynthesis. This study delved into transcriptomic changes in Begonia semperflorens leaves under varying light intensities: 950–9600 lx (TL_100), 6800–7000 lx (HS_75), and 4300–4500 lx (LS_25). To confirm the expression profiles of the key genes, we chose 12 critical genes associated with anthocyanin production for quantitative reverse transcription PCR (qRT-qPCR) analysis. Following this, we measured the levels of anthocyanins to substantiate the findings from the gene expression analysis. The transcriptome assembly in this study was extensive, yielding 43,038 unigenes that collectively spanned about 49.83 million base pairs, with an average unigene length of 1157 bp and an N50 value of 1685 bp. This assembly facilitated a thorough functional annotation across seven distinct protein databases, leading to the classification of 16,363 unigenes into 58 different families of transcription factors. Our comparative analysis of the transcriptomes highlighted a substantial number of differentially expressed genes (DEGs): 5411 DEGs between HS_75 and TL_100 conditions, with 3078 showing increased expression and 2333 showing decreased expression; 4701 DEGs between LS_25 and TL_100, consisting of 2648 up-regulated and 2053 down-regulated genes; and 6558 DEGs between LS_25 and HS_75, with 3032 genes up-regulated and 3526 down-regulated. These DEGs were significantly involved in critical pathways, such as anthocyanin synthesis, plant hormone signaling, and other regulatory mechanisms. This study suggests that genes, including F3′H, MYB102, and SWEET1, could play vital roles in regulating anthocyanin synthesis in response to various light conditions, potentially impacting the expression levels of other genes, like WRKYs, ATHB12, and those similar to HSP.